A computational framework for detecting malicious actors in communities. (1st January 2014) - Zhan, Justin; Fang, Xing
Despite the significant research achievements on the study of communities, how to maintain a benign social environment for a community, as a problem, has not received much attention. Current existing malicious activity detecting mechanisms are subject to the limitation of the underlying online environment. However, we found that information plays an important role in terms of socialisation. Malicious activities, like diffusing unreliable information and providing inappropriate critics, can severely impact the situation of a community's social environment. In this paper, we propose a computational framework for detecting malicious actors in communities from the perspective of information diffusion. We use the term, 'malicious actors', to represent a group of people who intentionally or unintentionally conduct malicious behaviours to sabotage benign social environments of communities.